Die Bedeutung von Schilddrüsenfunktionsstörungen in der Kinder- und Jugendgynäkologie - Dunstheimer, D.; Fahlbusch, C.; Hoyer-Kuhn, H.; Lehmann-Kannt, S.; Schenk, J.; Delisle, Birgit (Pädiatrische Praxis, 2022)
If women with severe thyroid disease become pregnant, there is a risk of abortion, stillbirth and fetal loss. Thyroid function has to be well controlled during pregnancy to avoid severe problems for them other as well as for the fetus. Screening of newborn children of TSH can detect the most thyroid diseases and is well treated. Without treatment in childhood there is a risk of abnormal mental and somatic development. In puberty acquired thyroid disease are more often and can lead to disturbance of puberty. Thyroid disorder are associated with irregular cycles and reduced fertility.
CRIS-Team Scopus Importer:2024-12-16
Keywords: graves’ disease; hypothyroidism; TSH neonatal screening